The psychological perception of the glass menagerie from author’s perspective - Omid Tabatabaei; Maryam Mohammadi Sarab (Politeknik Negeri Bali, 2020)
The ambiguities and interpretations, and perceptions of a content-based work psychologically and critically can be occurred for clarifying of the cognition, insight, and vision of the individual learners in their own learning especially in language learning. These conditions are usually viewed in real novels affecting the learning process in term of psychological understanding of the conceptual meanings of the text interpretation. The present review paper is based on the assimilation of the main author and the researcher’ perspective and perception of a real story. Thus, the creative approaches in language teaching can attract particular attention to the realistic perception of a text. As a result, the aim of the present study is to criticize and assimilates the place of characters of the book based on ‘relevance-theory’ to foster learner's perception, self-absorption, self-abnegation in a content-based study. This study is an exclusive one which is likely to personalize and animate the elements of the book.